Analisis Status Daya Dukung Air di Sub DAS Cikeruh, Jawa Barat Berdasarkan Neraca Air Meteorologis Thornthwaite-Mather - Rizky Ayu Aalimah; Sophia Dwiratna Nur Perwitasari; Edy Suryadi (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2022)
The results of population growth, regional development, and the rising infrastructure development are indirectly or directly linked to the cause of a decline in environmental carrying capacity, especially the unavoidable water resource carrying capacity. This research aims to analyze the current condition of water resource carrying capacity based on the Thornthwaite-Mather meteorological water balance model. The research is done in Cikeruh Sub-Watershed, Citarum Upstream Watershed with a total area of 19.143,21 ha, The research methods used are descriptive research with a quantitative approach, by analyzing the current condition of water resource carrying capacity that refers to the water resource capacity and the and the water resources needed for the domestic, non-domestic, agricultural, industrial, livestock and fishery sectors. The results of the research have shown an overshoot of water resource carrying capacity in 2020 within the research area. Those condition has shown that the water balance is in a deficit condition given that the water availability index has reached up to 193.583.337,01 m3/year and the water demand for those 6 sectors has reached up to 462.306.728,53 m3/year. Based on the result, in terms of quantity, the water availability index in the research area is still inadequate to fulfill the demand of those six sectors. Based on the analysis, the availability of water resources in Cikeruh Sub-Watershed is only adequate to fulfill the demands of water for domestic, non-domestic, livestock, fishery sectors, and agricultural sectors but are still inadequate for industrial.